Organic light emitting diode devices: An energy efficient solid state lighting for applications. (November 2020) - Pode, Ramchandra
Abstract: Electricity consumption for lighting is over 15% world's total electricity, thereby contributing to the 5% of worldwide greenhouse gas emissions. By 2030, a 50% rise in lighting demand of the existing consumption is projected due to an increase in the global population. To address the concern of rising lighting electricity consumption, the key strategy is to develop and provide energy efficient lighting products to consumers. In this respect, the Solid-State Lighting (SSL) has the potential to offer power efficiencies that are superior to those of conventional lighting sources. Recently, white organic light emitting devices (OLEDs) have emerged as the leading technology for the new display and lighting market which has attracted substantial attention of manufacturers, product designers, and end users. OLED devices have already entered into high end lighting markets such as designer, automotive, aerospace, high-end architectural lighting, and other applications. Moreover, innovative flexible OLED devices are thought to be candidates for the next-generation SSL systems, wearable electronics, mobile devices, microdisplays, etc. as they are lighter, thinner and more durable compared to glass (rigid) based devices. In the present review, distinctive features of OLEDs SSL lighting, technical requirements of lighting for applications, OLED basic, and classification of OLED devices, including quantum dot (QD) OLEDs (QLED) as well as the need of development of OLEDs standards are discussed. Various constituents of flexible OLED lighting, OLED lighting panels by some manufacturers, hurdles in OLED lighting technologies, performance of OLEDs in harsh conditions, challenges in flexible OLEDs, OLED lighting technology comparison, OLED lighting roadmap, and future directions including cost reduction analysis, flexible OLED incorporated into automotive, IoT (Internet of Things) connected lighting system, OLED market projections, etc. are also presented. It is suggested that the white OLEDs, and flexible OLEDs in particular, lighting products have potential to revolutionize the future of lighting systems, industries, and the market. Graphical abstract: Graphical representation: OLED lighting technology roadmap. Image 1 Highlights: Transition to energy efficient SSL sources offer 50% more light consuming 50% less electricity. Unique features of OLED lighting systems are area light source, no blue light hazard, and flexible/foldable products. Significant contribution to sustainability due to their environmentally friendly materials. Potential applications in architectural, hospitality, automotive sectors, and IoT connected lighting systems. Flexible OLEDs are expected to revolutionize lighting industries.